Apathy in Parkinson's disease: clinical features, neural substrates, diagnosis, and treatment. Issue 5 (May 2015) - Pagonabarraga, Javier; Kulisevsky, Jaime; Strafella, Antonio P; Krack, Paul
Summary Normal maintenance of human motivation depends on the integrity of subcortical structures that link the prefrontal cortex with the limbic system. Structural and functional disruption of different networks within these circuits alters the maintenance of spontaneous mental activity and the capacity of affected individuals to associate emotions with complex stimuli. The clinical manifestations of these changes include a continuum of abnormalities in goal-oriented behaviours known as apathy. Apathy is highly prevalent in Parkinson's disease (and across many neurodegenerative disorders) and can severely affect the quality of life of both patients and caregivers. Differentiation of apathy from depression, and discrimination of its cognitive, emotional, and auto-activation components could guide an individualised approach to the treatment of symptoms. The opportunity to manipulate dopaminergic treatment in Parkinson's disease allows researchers to study a continuous range of motivational states, from apathy to impulse control disorders. Parkinson's disease can thus be viewed as a model that provides insight into the neural substrates of apathy.